OPTIMIZING MEDICAL DEVICE MANUFACTURING INVENTORY MODEL FOR DETERIORATING ITEMS IN TWO WAREHOUSES USING FIFO POLICY - Mohammed Abid, Ajay Singh Yadav (South Eastern European Journal of Public Health, 2025)
The Medical Device Manufacturing’s two-warehouse inventory model for spoiled items in the event of shortages and inflation under the FIFO shipping policy addresses the challenges of inventory management in the Medical Device Manufacturing. This mathematical model combines theories of inventory management, spoilage, shortages and inflation to optimize inventory decisions. The model is based on the FIFO principle to ensure that the oldest inventory is shipped first, minimizing the risk of spoilage. Dairy expiration rates are considered to determine optimal restocking and shipping policies. The model also takes into account the possibility of bottlenecks and aims to minimize them through effective inventory management. In addition, inflation is taken into account to reflect changes in the economic environment and its impact on inventory costs. By applying mathematical techniques and optimization algorithms, the model helps to minimize total inventory costs and improve operational efficiency in the Medical Device Manufacturing. This summary provides an overview of the key elements and theoretical underpinnings of the Medical Device Manufacturing’s two-store inventory model and highlights its importance in improving inventory management practices.